2021
DOI: 10.1021/acs.langmuir.1c01329
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Propulsion of Magnetic Dimers under Orthogonally Applied Electric and Magnetic Fields

Abstract: Anisotropic particles have been widely used to make micro/nanomotors that convert chemical, ultrasonic, electrical, or magnetic energy into mechanical energy. The moving directions of most colloidal motors are, however, difficult to control. For example, asymmetric dimers with two lobes of different sizes, ζ-potential, or chemical composition have shown rich propulsion behaviors under alternating current (AC) electric fields due to unbalanced electrohydrodynamic flow. While they always propel in a direction pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 44 publications
(79 reference statements)
0
13
0
Order By: Relevance
“…In the rotating magnetic field, the rotation speed of the Fe 3 O 4 /f-C 3 N 4 motor increases as the frequency of the magnetic field increases up to 9 Hz. Due to the viscous resistance, the rotation speed declines with increasing frequency of the magnetic field at higher frequencies (Figure c) as the motor fails to follow the external magnetic field Figure d shows the snapshots of a Fe 3 O 4 /f-C 3 N 4 micromotor rotating in a rotary magnetic field of 1 Hz and 3 mT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the rotating magnetic field, the rotation speed of the Fe 3 O 4 /f-C 3 N 4 motor increases as the frequency of the magnetic field increases up to 9 Hz. Due to the viscous resistance, the rotation speed declines with increasing frequency of the magnetic field at higher frequencies (Figure c) as the motor fails to follow the external magnetic field Figure d shows the snapshots of a Fe 3 O 4 /f-C 3 N 4 micromotor rotating in a rotary magnetic field of 1 Hz and 3 mT.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the viscous resistance, the rotation speed declines with increasing frequency of the magnetic field at higher frequencies (Figure 5c) as the motor fails to follow the external magnetic field. 57 Figure 5d shows the snapshots of a Fe 3 O 4 /f-C 3 N 4 micromotor rotating in a rotary magnetic field of 1 Hz and 3 mT. 40,54 The mechanism for the increased reaction kinetics under a rotary magnetic field is further explored.…”
Section: Characterization Of the Samplesmentioning
confidence: 99%
“…The special arrangement of two (dimer) or more (chain) touching spherical particles often occurs in many branches of mathematical physics and nanotechnology, such as electrostatic [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ] and optics [ 22 , 23 , 24 , 25 ]. The tangent-sphere coordinate system can be effectively used for analytically tackling some related problems involving particle-wall interactions in various electrokinetic [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ], heat transfer [ 36 , 37 , 38 ], inviscid [ 39 , 40 , 41 , 42 , 43 ], and viscous [ 44 , 45 , 46 , 47 , 48 , 49 , 50 ] flow scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Further, asymmetric colloidal dimers [10] and also metallo-dielectric Janus particles [11] placed on an electrode and subjected to a vertical electric field are propelled perpendicularly to the electric field in a random direction in the 2D plane defined by their current orientation. Within this setup, magnetic fields have been used in combination with ferromagnetic metallo-dielectric Janus particles [12] and ferromagnetic asymmetric colloid dimers [13] to introduce maneuverability. Further, it has been demonstrated that metallo-dielectric Janus particles can be used to transport other dielectric particles.…”
Section: Introductionmentioning
confidence: 99%
“…Within this setup, it was demonstrated that asymmetric colloidal dimers [9] and metallo-dielectric Janus particles [10] are propelled perpendicularly to the electric field in a random direction in the 2D plane. To introduce maneuverability, magnetic fields have been used in combination with ferromagnetic metallo-dielectric Janus particles [11] and ferromagnetic asymmetric colloidal dimers [12]. Further, it has been demonstrated that metallodielectric Janus particles can be used to transport other dielectric particles [11, 13, 14].…”
mentioning
confidence: 99%